High-Frequency Percussive Ventilation: A New Strategy for Separation from Extracorporeal Membrane Oxygenation. (1st April 2015) - Boscolo, Annalisa; Peralta, Arianna; Baratto, Fabio; Rossi, Sandra; Ori, Carlo
Abstract : We report the case of a 48-year-old woman who developed severe septic shock and lung injury after community-acquired pneumonia. She was supported on arteriovenous extracorporeal membrane oxygenation (ECMO) for 19 days. To facilitate decannulation and separation from ECMO, we began trials of high-frequency percussive ventilation (HFPV) using the volumetric diffusive respiration ventilator VDR-4 (Percussionaire Corp, Sandpoint, Idaho) for 4 consecutive days (1 before and 3 after). Decannulation was achieved successfully, and the patient was transferred to the floor 3 months later. During the 4 days of HFPV, the chest radiograph improved, as did gas exchange and clearance of pulmonary secretions. HFPV may be a promising strategy for improving lung recruitment and airway clearance during separation from ECMO in the critically ill patient.